2006
DOI: 10.4049/jimmunol.176.4.2546
|View full text |Cite
|
Sign up to set email alerts
|

Impaired GATA3-Dependent Chromatin Remodeling and Th2 Cell Differentiation Leading to Attenuated Allergic Airway Inflammation in Aging Mice

Abstract: Age-related changes in lymphocytes are most prominent in the T cell compartment. There have been substantial numbers of reports on T cell function in aged mice and humans, such as on the production of Th1 and Th2 cytokines, but the results show considerable variation and contradictions. In the present study, we used 8- to 12-mo-old aging mice and a well-established in vitro Th1/Th2 cell differentiation culture system to identify molecular defects in Th1/Th2 cell differentiation that can be detected in the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…However, the effects of the aging process on inflammation associated with asthma have not been clarified. Some previous studies have reported that older antigen-sensitized and -challenged animals have a lower total cell count and eosinophils percentage in BAL fluid, and suppressed Th2 cytokines compared with young mice 2–4. However, recent data has shown that older OVA mice display greater inflammation compared with young 6-week-old mice 5,21.…”
Section: Discussionmentioning
confidence: 95%
“…However, the effects of the aging process on inflammation associated with asthma have not been clarified. Some previous studies have reported that older antigen-sensitized and -challenged animals have a lower total cell count and eosinophils percentage in BAL fluid, and suppressed Th2 cytokines compared with young mice 2–4. However, recent data has shown that older OVA mice display greater inflammation compared with young 6-week-old mice 5,21.…”
Section: Discussionmentioning
confidence: 95%
“…To date, the precise mechanisms of the development of respiratory tolerance in mice repeatedly challenged with OVA aerosols have not been elucidated, and both regulatory T cell-dependent [36] and regulatory T cell-independent [37] mechanisms have been proposed. One factor that may be important in the down-regulation of allergic airway inflammation and AHR over time could be the aging of mice, because some studies found that the capability of T cells to differentiate into Th-2 cells was reduced in aging mice [38, 39]. In contrast, one recent study found that older mice developed increased allergic inflammation, but less pronounced AHR [40].…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + T cells isolated from lamina propria were labeled with CFSE (Invitrogen) as described previously [52]. The cells were cultured in complete medium in the presence of Con A (2 µg/ml) (WAKO, Osaka, Japan) for 48 h, and then were analyzed on a FACSCalibur instrument (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%